Nutritional Evaluation of Pediatric Patients with Sickle Cell Disease Treated with Hydroxyurea - Belkis Lázara Rodríguez Jorge; Lucía Morejón Díaz; Yoandra León Rayas; María Santa Cruz (Revista Finlay)
Background: clinical studies in patients with sickle cell disease have shown that the use of hydroxyurea is associated with a reduction in acute and chronic complications, including those related to the nutritional status of these patients. Objective: to evaluate the nutritional status in patients with sickle cell disease treated with hydroxyurea at the Paquito González Cueto University Pediatric Hospital in Cienfuegos. Methods: a descriptive, analytical and prospective study was carried out of all the patients with sickle cell disease treated with hydroxyurea, treated at the Hematology Service of the Pediatric Hospital of Cienfuegos in the period from January 2012 to December 2018. The study variables were: age, sex, hemoglobin variant, clinical manifestations and nutritional evaluation, hematological parameters, hospitalizations and transfusion requirements. The information was obtained from the clinical records. Results: 15 patients were studied, there was a predominance of females (60 %) and adolescents represented 80 % of the patients in the study. 10 patients (66.7 %) presented the homozygous form; the Sβ thalassemia and SC variant were represented with 2 and 3 patients, respectively. There were no significant differences when comparing hematological values before and after treatment. A decrease was observed in the frequency and severity of the seizures, in the number of hospitalizations and transfusion requirements in all the patients. Malnutrition was present in only 4 patients out of the total. Conclusions: treatment with hydroxyurea for the study patients resulted in clinical improvement, reduction in the number of admissions and decrease in transfusion requirements, which favorably affected their nutritional status.